امت مسلمہ کی بحالی اور اقبال کا فلسفہ تعلیم و عمل: ڈاکٹر عبدالحق کے نقطۂ نظر کا جائزہ: Restoration of Muslim Ummah and Iqbal’s Philosophy of Education and Practice: Dr. Abdul Ḥaq’s Perspective (Al-Qamar, 2020)
Prof. Dr. Abdul Haq is a well-known Iqbal scholar. He has been the President of the Department of Urdu, Delhi University. He has written more than 40 books. In recognition of his scholarly services, he was awarded the title of Professor Emeritus. Among the aspects of Iqbal's thought which he has highlighted regarding the rebirth of the Muslim Ummah, the subject of education is at the forefront. Iqbal is a staunch supporter of modern education and seems to emphasize the need and importance of self-training and character building along with education. He is in favor of formulating a curriculum for the Muslim Ummah which will play a key role in instilling in them a sense of self and a sense of earthly caliphate. Another aspect of the revival of the Muslim Ummah is the acquisition of power. The source of gaining power lies in the philosophy of jihad, by following which man can fight the internal and external forces of evil. The last thing that Dr. Abdul Haq has drawn from Iqbal's thought is the philosophy of action. Muslims will be able to maintain their identity only after playing their full role in the field of science and technology.
Keywords: Iqbal's Thought; modern education; self-Training; curriculum; acquisition; philosophy; Science; technology